FAKTOR-FAKTOR YANG MEMPENGARUHI WUS (WANITA USIA SUBUR) DALAM PEMERIKSAAN PAP SMEAR DI PUSKESMAS SELESAI TAHUN 2017 - Nurhafni Nurhafni (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2017)
Cancer is one of the biggest causes of death in this century. In general, cancer can attack almost every part of the human body, among the most likely to be affected by cancer is the female reproductive system, one of which is the cervix. Cervical cancer (cervical cancer) is a gynecological malignancy that causes problems in women's health, especially in developing countries. This cancer begins to be found at the age of 25-34 years and peak at age 45-54 years. The purpose of this study was to determine the relationship of factors affecting WUS (Fertile Age Women) in Pap Smear examinations at the Health Center Completed in 2017. This type of research is descriptive analytic. The population and sample of the study were 34 WUS (Fertile Age Women) in the Puskesmas Completed in 2017. The data used were primary and secondary data. Data were analyzed by univariate and bivariate. The results showed that the knowledge and attitude variables of pregnant women Knowledge, Gender, Distance, Motivation, Husband Support had a significant relationship with the variable Pap Smear Examination. These results conclude that there is a relationship between distance to health services and Pap Smear examination at the Health Center Completed in 2017. It is expected that WUS (Fertile Age Women) can increase people's knowledge, especially WUS (Fertile Age Women) so that they are motivated to do pap smear examinations.